2005
DOI: 10.1007/s00441-004-1009-0
|View full text |Cite
|
Sign up to set email alerts
|

Colocalization of GH, TSH and prolactin, but not ACTH, with ?LH-immunoreactivity: evidence for pluripotential cells in the ovine pituitary

Abstract: Increasing evidence suggests that multihormonal cells in the pituitary gland may be more commonplace than previously thought. This has forced us to reconsider our classical view of cell populations in the pituitary gland. Studies so far have focused almost exclusively on the rat, and there is a dearth of information on other species. Our first objective was to determine whether a subpopulation of gonadotropes also express somatotropin in the ewe, as reported in the rat. In addition, we sought to determine whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 57 publications
1
17
1
Order By: Relevance
“…This corroborates previous studies in BS ewes and in mice, and highlights a species difference in the prevalence of co-expression, as in contrast to sheep which showed a 10% co-expression in the PD [34], almost 41% of the mouse thyrotrophs were found to co-express LHB protein and secrete LH [35]. Whilst historically such cells are considered to represent an intermediate step in the trans-differentiation process, they are observed in the normal, resting gland where the rate of trans-differentiation is low.…”
Section: Discussionsupporting
confidence: 80%
“…This corroborates previous studies in BS ewes and in mice, and highlights a species difference in the prevalence of co-expression, as in contrast to sheep which showed a 10% co-expression in the PD [34], almost 41% of the mouse thyrotrophs were found to co-express LHB protein and secrete LH [35]. Whilst historically such cells are considered to represent an intermediate step in the trans-differentiation process, they are observed in the normal, resting gland where the rate of trans-differentiation is low.…”
Section: Discussionsupporting
confidence: 80%
“…We have reported the specificity of the GH antibody previously [29]. The substance P antibody was preadsorbed with 10 lg/ml substance P (American Peptide Co, Sunnyvale, CA) and no staining was evident (data not shown).…”
Section: Dual Labelingmentioning
confidence: 96%
“…The PT-specific secretory cells contain a small number of secretory granules and aggregate or scatter glycogen particles (Morgan and Williams, 1996;Yasuo and Korf, 2011). It was established that gonadotrophs from the PT may contain and secrete some amount of the luteinizing hormone (LH) and follicle stimulating hormone (FSH) (Mignot and Skinner, 2005;PerezCastro et al, 2012). Colocalization of LH and other hormones like prolactine, growth hormone (GH) and thyroid-stimulating hormone (TSH) was immunocytochemically demonstrated by Mignot and Skinner (2005).…”
Section: Introductionmentioning
confidence: 99%
“…It was established that gonadotrophs from the PT may contain and secrete some amount of the luteinizing hormone (LH) and follicle stimulating hormone (FSH) (Mignot and Skinner, 2005;PerezCastro et al, 2012). Colocalization of LH and other hormones like prolactine, growth hormone (GH) and thyroid-stimulating hormone (TSH) was immunocytochemically demonstrated by Mignot and Skinner (2005). Additionally, some studies showed that the PT can release factors which can modulate the activity of the PD lactotrophs (Lafarque et al, 2004).…”
Section: Introductionmentioning
confidence: 99%